1970
DOI: 10.1073/pnas.66.1.153
|View full text |Cite
|
Sign up to set email alerts
|

Dolichol Monophosphate Glucose: An Intermediate in Glucose Transfer in Liver

Abstract: Abstract. The microsomal fraction of liver has been found to catalyze glucose transfer from UDPG to a lipid acceptor which appears to be identical to the compound obtained by chemical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0

Year Published

1971
1971
2006
2006

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 243 publications
(62 citation statements)
references
References 14 publications
2
60
0
Order By: Relevance
“…Dol-P was isolated and purified up to the DEAE-cellulose step [5]. D o~-P -[~~C ] G~C was prepared by incubation of UDP-[14C]Glc with liver microsomes and purified by DEAE-cellulose chromatography [5,6]. Dol-P-P-Glc-oligosaccharide labelled in the glucose or in the mannose was obtained by incubation of microsomes with UDP-['4C]G1~ [7] Abbreviations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dol-P was isolated and purified up to the DEAE-cellulose step [5]. D o~-P -[~~C ] G~C was prepared by incubation of UDP-[14C]Glc with liver microsomes and purified by DEAE-cellulose chromatography [5,6]. Dol-P-P-Glc-oligosaccharide labelled in the glucose or in the mannose was obtained by incubation of microsomes with UDP-['4C]G1~ [7] Abbreviations.…”
Section: Methodsmentioning
confidence: 99%
“…Dol-P was isolated and purified up to the DEAE-cellulose step [5]. D o~-P -[~~C ] G~C was prepared by incubation of UDP-[14C]Glc with liver microsomes and purified by DEAE-cellulose chromatography [5,6].…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, dolichol is more widely distributed within the cell and in different tissues and organs. Dolichol was first identified in 1960 by Pennock, Hemming & Morton [1], and it was established by Behrens & Leloir in 1970 [2] that its phosphorylated derivative is an obligatory intermediate in the synthesis of certain types of glycoproteins. Of all lipids, this compound has thus been studied for the shortest period of time and, despite detailed investigations in many laboratories in recent years, our knowledge about the biosynthesis, distribution and function of dolichol is still fragmentary.…”
Section: Introductionmentioning
confidence: 99%
“…In the first paper on the formation of dolichol monophosphate glucose (dolichol-P-Glc) it was reported that the glucosyl residue of this substance was transferred to an endogenous acceptor on further incubation with liver microsomes (1). The product thus formed was believed to be a glycoprotein because of its insolubility in certain organic solvents and in trichloroacetic acid.…”
mentioning
confidence: 99%